Polypectomy of Esophageal Polyp due to Esophagitis - Ari Fahrial Syam; Marcellus S. Kolopaking; Chudahman Manan (The Indonesian Society for Digestive Endoscopy, 2002)
Esophageal polyp can be found by chance during endoscopic examination. Polyps can be formed by changes in the esophageal mucosa due to reflux esophagitis. We report a case of multiple esophageal polyp in a patient with complaints of recurrent regurgitation without heartburn. Endoscopy demonstrated multiple polyps at the distal esophagus. Anatomic pathology evaluation of the polyp demonstrated mucosa lined with squamous epithels demonstrating elongation of the papilla and deposition of acute and chronic inflammatory cells, indicating chronic esophagitis with hyperplastic epithels. In this case, we conducted recurrent ligation of the multiple polyps. Evaluation at 2 weeks after the final ligation demonstrated no polyp remains, and the post-ligation ulcer was found. Evaluation at 1 month following treatment found diminished complaints. From this case, we can conclude that endoscopy is an important investigation modality to establish the diagnosis in cases of chronic gastrointestinal complaints. Ligation is a choice for the management of esophageal polyps. Key words: Esophageal polyp, polipectomy, ligation